2017
DOI: 10.1371/journal.pone.0175852
|View full text |Cite
|
Sign up to set email alerts
|

Apomixis frequency under stress conditions in weeping lovegrass (Eragrostis curvula)

Abstract: To overcome environmental stress, plants develop physiological responses that are triggered by genetic or epigenetic changes, some of which involve DNA methylation. It has been proposed that apomixis, the formation of asexual seeds without meiosis, occurs through the temporal or spatial deregulation of the sexual process mediated by genetic and epigenetic factors influenced by the environment. Here, we explored whether there was a link between the occurrence of apomixis and various factors that generate stress… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
65
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(77 citation statements)
references
References 55 publications
8
65
0
Order By: Relevance
“…Results support the hypothesis that the oxidative lesions might mobilize the meiotic DNA repair system in the megaspore mother cell and trigger meiosis and megasporogenesis (Hörandl and Hadacek, 2013). This stimulus might increase the proportion of functional megaspores as a cellular survival strategy for the germline (Rodrigo et al, 2017), as shown remarkably in our diploids. Differential genetic stress regulation of sexual and apomictic plants was also observed in seedlings of Boechera, and may be important for the bypass of the meiotic pathway (Shah et al, 2016).…”
Section: Effects Of Ploidy Treatment and Combined Effect Of Ploidy/supporting
confidence: 89%
See 3 more Smart Citations
“…Results support the hypothesis that the oxidative lesions might mobilize the meiotic DNA repair system in the megaspore mother cell and trigger meiosis and megasporogenesis (Hörandl and Hadacek, 2013). This stimulus might increase the proportion of functional megaspores as a cellular survival strategy for the germline (Rodrigo et al, 2017), as shown remarkably in our diploids. Differential genetic stress regulation of sexual and apomictic plants was also observed in seedlings of Boechera, and may be important for the bypass of the meiotic pathway (Shah et al, 2016).…”
Section: Effects Of Ploidy Treatment and Combined Effect Of Ploidy/supporting
confidence: 89%
“…The high variability of the proportions of sexual ovules among our genetically identical polyploids supports the findings of epigenetic and transcriptional control mechanisms as the background for the phenotypic expression of apospory (Grimanelli, 2012;Schmidt et al, 2014). Our result supports the hypothesis that phenotypic features of apomixis in flowering plants are strongly affected by polyploidy (Delgado et al, 2016;Kaushal et al, 2018) and subjected to epigenetic control (Rodrigo et al, 2017).…”
Section: Effects Of Ploidy Treatment and Combined Effect Of Ploidy/supporting
confidence: 87%
See 2 more Smart Citations
“…Attempts to identify components of apomixis by transcriptional profiling of reproductive organs using Differential Display PCR (DD-PCR), SuperSAGE (serial analysis of gene expression), and high-throughput sequencing on microdissected ovules revealed 1) differentially expressed genes in reproductive tissues of apomictic and sexual relatives from different plant systems (e.g., Pennisetum, [69,70]; Brachiaria, [71,72]; Panicum, [73,74]; Poa, [75], Eragrostis, [76][77][78]; Paspalum, [42,64,[79][80][81]; Hieracium, [82,83]; Hypericum [84,85]) and 2) an overall shift in gene regulation at the MMC stage and a global heterochronic gene expression between the sexual and apomeiotic ovules (e.g., Boechera, [86][87][88][89]; Paspalum [79,90,91]; Pennisetum, [92]; Hieracium, [83,93,94]; Hypericum [85,95]; Ranunculus [96,97]). Such wide-ranging de-regulation on gene expression levels between sexual and apomictic ovules affect genes encoding varied biological functions (GO classes) and regulatory pathways, including key genes of the sexual pathway, RNA-directed DNA methylation and transcription regulation, hormonal signaling, and cell cycle control (see details in the next section).…”
Section: Genetic and Genomic Features Of Apomixismentioning
confidence: 99%